2023
DOI: 10.3390/ijms241512025
|View full text |Cite
|
Sign up to set email alerts
|

The Sigma Receptors in Alzheimer’s Disease: New Potential Targets for Diagnosis and Therapy

Abstract: Sigma (σ) receptors are a class of unique proteins with two subtypes: the sigma-1 (σ1) receptor which is situated at the mitochondria-associated endoplasmic reticulum (ER) membrane (MAM), and the sigma-2 (σ2) receptor, located in the ER-resident membrane. Increasing evidence indicates the involvement of both σ1 and σ2 receptors in the pathogenesis of Alzheimer’s disease (AD), and thus these receptors represent two potentially effective biomarkers for emerging AD therapies. The availability of optimal radioliga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 255 publications
(344 reference statements)
0
5
0
Order By: Relevance
“…However, aryl fluorides are usually rather stable in vivo, while alkyl fluorides carry the risk of defluorination, which would result in bone labeling via the formation of [ 18 F]CaF 2 . Several PET tracers bearing aromatic and aliphatic fluorine-18 have been reported in the literature [ 16 , 22 , 23 ].…”
Section: Fluorinated Pet Tracers Derived From the Promising σ ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, aryl fluorides are usually rather stable in vivo, while alkyl fluorides carry the risk of defluorination, which would result in bone labeling via the formation of [ 18 F]CaF 2 . Several PET tracers bearing aromatic and aliphatic fluorine-18 have been reported in the literature [ 16 , 22 , 23 ].…”
Section: Fluorinated Pet Tracers Derived From the Promising σ ...mentioning
confidence: 99%
“…It was hypothesized that the activation of σ 1 receptors by donepezil contributes to its neuroprotective and anti-amnesic effects [ 15 ]. In PET studies, a low σ 1 receptor density was found for patients at an early stage of Alzheimer’s disease [ 16 ].…”
Section: Introduction: the Role Of σ 1 Receptors I...mentioning
confidence: 99%
“…This occurs at three levels: cholesterol synthesis, cholesterol uptake in the form of LDL, and cholesterol release from lysosomes following autophagy or LDLR-mediated endocytosis of LDL (reviewed in Refs. [10,11,13,20,21]). The biosynthesis of cholesterol is controlled by SREBP-2, which induces the expression of HMG-CoA reductase, the rate-limiting enzyme in cholesterol synthesis, and the expression of LDLR.…”
Section: Function Of S2r In Cholesterol Homeostasis and Its Potential...mentioning
confidence: 99%
“…This functional connection and the substantial sharing of the ligands form the basis to group all four proteins under the umbrella term "sigma receptors". There are several outstanding in-depth reviews on the historical, pharmacological, biological, and structural aspects of these four proteins, authored by experts in this field [9,11,[16][17][18][19][20][21]. The goal of this present review is to provide a synopsis of the structural features of these proteins based on the most recent discoveries in the field and then to focus on the interesting roles of these proteins in iron/heme metabolism and homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that sigma receptor ligands can elevate Ach extracellular levels in prefrontal cortex rat brain [ 6 , 7 ]. Given the high sigma-1 receptor affinity of fluoxetine, this selective serotonin reuptake inhibitor (SSRI), which is commonly used to treat depression, attracts attention for managing cognitive deficits in AD [ 8 , 9 , 10 ]. Indeed, there is a growing evidence showing the neuroprotective effect of fluoxetine against amyloid beta Aβ plaques and hyperphosphorylated tau tangles, as the hallmark pathological features of AD and tau pathology [ 11 ].…”
Section: Introductionmentioning
confidence: 99%